Desain Sistem Pengolaha Tepung MOCAF (Modified Cassava) Menggunakan Software PLC OMRON - Pratama, Rifki Adi; Pertiwi, Kisna; Sabar, Sabar (Universitas Mulawarman, 2024)
This research aims to design and develop a Mocaf (Modified Cassava Flour) processing system based on automation using Omron PLC software. Mocaf flour is a cassava-derived product whose processing involves fermentation, drying, and milling stages. The designed system focuses on improving production efficiency, maintaining product quality, and minimizing errors caused by human factors. The research method includes system requirements analysis, hardware and software design, as well as implementation and testing on a prototype. The Omron PLC serves as the main controller, integrating various sensors and actuators to monitor and control the processes automatically. The system is also equipped with a user interface to facilitate process monitoring and parameter settings. The results indicate that the designed system can optimize the Mocaf flour production process with high precision and reliability. Additionally, the use of Omron PLC-based automation has proven effective in reducing processing time and increasing productivity. This research is expected to contribute to the development of a more modern and efficient local food industry.